Clouds in the Vicinity of the Stratopause Observed with Lidars at Midlatitudes (40.5–41°N) in China - Shaohua Gong; Yuru Wang; Jianchun Guo; Weipeng Chen; Yuhao Zhang; Faquan Li; Yuchang Xun; Jiyao Xu; Xuewu Cheng; Guotao Yang (Remote Sensing, 2022)
Based on long-term lidar (light detection and ranging) observations at Yanqing (40.5°N, 116°E) and Pingquan (41°N, 118.7°E), cloud events occurred in the vicinity of the stratopause above Beijing were reported for the first time. These events occurred with tenuous and sparse layers within the altitude range of 33–65 km, and the maximum VBSC value ranged from <semantics>1×10−10m−1sr−1</semantics> to <semantics>5.5×10−9m−1sr−1</semantics>. Considering temperature and water vapor measurements from SABER/TIMED, the occurrence mechanism of these lidar-observed cloud events was examined. It was found that some cloud layers resulted from the nucleation of water vapor due to the local meteorological changes in the middle atmosphere, while other lidar-observed clouds could comprise floating clusters of cosmic dust, hydrate droplets, volcanic ash, space traffic exhaust, etc. These cloud events are rare cloud-like phenomena in the middle atmosphere observed by lidars at midlatitudes in China; they differ from NLCs and PSCs in terms of altitude distribution and seasonal variation, and the relevant microphysics processes behind their occurrence are likely meaningful to meteorology at midlatitudes.